2021
DOI: 10.1177/23259671211049476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skeletal Maturity on Fixation Techniques for Tibial Eminence Fractures

Abstract: Background: Several fixation methods have been reported for the operative treatment of tibial eminence fractures. Previous biomechanical studies have demonstrated that suture fixation may be a stronger construct; however, the maturity status of these specimens was not scrutinized. Purpose: To examine if suture fixation remains a biomechanically superior fixation method to screw fixation in both skeletally mature and immature specimens. Study Design: Controlled laboratory study. Methods: Sixteen total matched p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Regarding screw fixations, Ye et al 36 recently conducted a meta-analysis of studies comparing single-screw fixation versus the FiberWire suture fixation described in our study, concluding that suture fixation was superior across the spectrum of biomechanical properties. 6,9,11,20,26,29 Eggers et al 9 and Thome et al, 34 who studied skeletally mature porcine knees, concluded that the ultimate failure load of 2-screw fixation was approximately half that of FiberWire suture fixation. However, Thome et al also reported equivalency between 2-screw and 2-suture fixation in skeletally immature porcine knees, providing the initial motivation for our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding screw fixations, Ye et al 36 recently conducted a meta-analysis of studies comparing single-screw fixation versus the FiberWire suture fixation described in our study, concluding that suture fixation was superior across the spectrum of biomechanical properties. 6,9,11,20,26,29 Eggers et al 9 and Thome et al, 34 who studied skeletally mature porcine knees, concluded that the ultimate failure load of 2-screw fixation was approximately half that of FiberWire suture fixation. However, Thome et al also reported equivalency between 2-screw and 2-suture fixation in skeletally immature porcine knees, providing the initial motivation for our study.…”
Section: Discussionmentioning
confidence: 99%
“…These low failure loads seen in pediatric specimens throughout this study have potential implications for postoperative rehabilitation protocols. For example, biomechanical studies in adults have found that in situ forces on the ACL-tibial spine complex can reach up kk References 2,3,6,9,15,20,[27][28][29]34,36. {{ to 303 N during early rehabilitation activities, such as contralateral toe-off during walking. 30 Because no reports of biomechanical forces on the pediatric ACL-tibial spine complex during early rehabilitation are available, we are unable to provide quantitative recommendations about the specific rehabilitation protocols that pediatric patients with TSFs should undergo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although screw fixation can provide strong fixation of the fracture fragment, previous biomechanical studies have shown that suture fixation had an even greater strength than cortical screws. 20 , 21 When comparing clinical outcomes, most studies have not shown a difference between screw and suture fixation, but have noted a higher risk for repeat surgery and need for hardware (screw) removal. 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 When comparing clinical outcomes, most studies have not shown a difference between screw and suture fixation, but have noted a higher risk for repeat surgery and need for hardware (screw) removal. 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%